Dermatoglyphics: Revival in oral pre-cancers and cancers, a review - N Lakshmana; Abhishek Singh Nayyar; A Ravikiran; Y Samatha; Vamsi B Pavani; B Kartheeki (Wolters Kluwer Medknow Publications, 2017)
Dermatoglyphics deals with the study of the epidermal ridges and their configurations on the fingers, palms, and soles. The word dermatoglyphics is derived from the Greek word derma meaning skin and glyphics meaning carvings. Dermatoglyphics, once matured, remain unchanged throughout the life of an individual and are not influenced by either the environmental or age-related factors. Because of these unique characteristics, these dermal ridges play a very crucial role in the personal identification of an individual, for forensic purposes. Dermatoglyphics has also been accepted as a simple and inexpensive means for deciding whether a patient would have a particular genetic or chromosomal disorder or not. The question, now, is to test the predictive possibilities of dermatoglyphics in search of the various oral precancers and cancers as the studies conducted so far have been convincing. The present review focuses on this aspect of dermatoglyphics.